Impact of quality management tools and techniques: Case of Namibian municipal water distributors. Issue 1 (12th March 2018) - Silombela, Timothy; Mutingi, Michael; Chakraborty, Ayon
Abstract : Purpose: The purpose of this paper is to provide an understanding on the impact of quality management (QM) tools and techniques in water supply infrastructure maintenance and the generation of non-revenue water (NRW) by Namibian Municipal Water Distributors. Design/methodology/approach: In-depth interviews were selected as the primary data collection method, while secondary data were collected using document review and observations. In-depth interviews as primary method provided rich data and details on the subject matter from the respondents. Document review and observations provided a holistic perspective and understanding of the context within which the maintenance projects are handled by municipal water distributors. Findings: The study found that as the number of QM tools employed to analyze maintenance data increases, the generation of NRW by the municipality decreases. However, for the tools to be effective, they should cover applications such as problem identification, data analysis, process analysis, decision making, planning, quality control and statistical process control, this helped Namibian municipalities to produce low volumes of NRW. In contrast, municipalities using QM tools arbitrarily lead to high quantities of NRW generation. Originality/value: The World Bank recommends that NRW should be less than 25 percent of the total water produced, while in many countries NRW is up to 60 percent. Developed economies have made efforts to reduce NRW but efforts are still at nascent stage in emerging economies. This is the first study providing evidences of QM tools application in maintenance process and effect on NRW.